2021
DOI: 10.1111/ijcp.14086
|View full text |Cite
|
Sign up to set email alerts
|

Radiological evaluation of maxillofacial soft tissue calcifications with cone beam computed tomography and panoramic radiography

Abstract: The maxillofacial region is composed of various anatomical structures that are observed as different densities on radiographs. In addition to teeth, bones and soft tissues, variations and pathological conditions also contribute to this density range. Radiographic interpretation may challenge practitioners to determine an exact diagnosis. It is difficult to diagnose calcifications caused by pathological conditions, especially areas that neighbour teeth and bone. 1,2 Idiopathic and dystrophic calcifications a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Demographic characteristics differ in patients with soft tissue calcifications/ossifications according to the population. In literature, some studies indicate that soft tissue calcification/ossification is more common in female [12,17], in some other studies is more common in male [18,19], while some other studies it is reported to no difference between the genders [8,16]. Soft tissue calcifications/ossifications are generally seen in patients over the age of 40, but they can also be seen in children [6,20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Demographic characteristics differ in patients with soft tissue calcifications/ossifications according to the population. In literature, some studies indicate that soft tissue calcification/ossification is more common in female [12,17], in some other studies is more common in male [18,19], while some other studies it is reported to no difference between the genders [8,16]. Soft tissue calcifications/ossifications are generally seen in patients over the age of 40, but they can also be seen in children [6,20].…”
Section: Discussionmentioning
confidence: 99%
“…Soft tissue calcifications/ossifications are generally seen in patients over the age of 40, but they can also be seen in children [6,20]. In three recent studies examining patients in Turkey, the mean age of patients with soft tissue calcification/ossification was 52.12 ± 17.62, 44.17 ± 16.04, 51.2 ± 15.6, respectively [8,12,19]. In these studies, it was reported that the patients with soft tissue calcification/ossification were mostly 40 years and older.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En ella, se puede realizar un análisis multiplanar dinámico que proporciona valiosa información para identificar de una forma más precisa estas calcificaciones, las cuales se identifican en la TCHC como pequeñas imágenes hiperdensas similares al hueso. Estas calcificaciones también se pueden observar en radiografías panorámicas, aunque la interpretación se hace compleja por la superposición de estructuras óseas (2,6,8).…”
Section: Señor Editorunclassified